Standardization of methods for preparation of pomegranate jam - Bhanj, Pooja Upasana; Mohapatra, Sipra; Roy, Manideepa; Das, Ankan (Journal of Postharvest Technology, 2021)
Fresh and fully matured pomegranate fruits were taken for the study of standardizing methods for preparation of jam with specified concentration of pectin of 15, 18 and 20% and sodium benzoate of 100 and 150 ppm respectively. Two heating techniques that is induction heating (I.H.) and microwave heating (M.H.) were used to prepare the jam. Thereafter different parameters such as total sugar, reducing sugar, total phenolic content, appearance score, and fungal count were analyzed at different day’s interval. The jam prepared were kept in sterilized glass jars and stored in refrigerated condition. All the treatments were replicated three times and two factorial Completely Randomized Design was used for statistical analysis. From the study it was observed that pomegranate prepared with 20 % pectin and 150 ppm sodium benzoate and jam with 15% pectin and 100 ppm of sodium benzoate were good and the microwave heating (M.H.) gave better results over induction heating (I.H.).